Intrastromal Keratolimbal Epithelial Cysts: Congenital and Postsurgical - Schoelles, Kristina Joana; Auw-Hädrich, Claudia; Maier, Philip Christian; Reinhard, Thomas (Klinische Monatsblätter für Augenheilkunde, 2022)
Two very rare cases of intrastromal keratolimbal epithelial cysts are reported. Firstly, an enlarging congenital cyst in a 9-year-old boy, and secondly, a recurrent postsurgical cyst in an 18-year-old female patient. Both cases presented with a limbal cyst, continuing into the corneal stroma as a whitish mass up to the optical axis. The indication for surgery was stabilization of visual acuity in case one and improvement of cosmetic aspects in case two. In the first case, a small part of the cyst was opened at the limbus and the whitish material in the cyst was flushed out. In the second case, anterior lamellar keratectomy over the whole cyst was performed with subsequent application of mitomycin C. Immunohistochemical analysis revealed cytokeratin 19-positive epithelial cells in both cysts. Therefore, an implantation of conjunctival epithelium into the sclera seems to be responsible for the respective keratolimbal cyst. Postsurgically, satisfying cosmetic and functional results were obtained in both cases, with follow-ups of 4 and 9 months. Keratolimbal cysts have rarely been described in the literature. In most cases, a conjunctival epithelial implantation occurs following surgery or trauma and very rarely congenitally. After simple aspiration of the cystʼs content, a rapid recurrence is often observed, so that partial or – if possible – complete removal of the anterior cyst wall is recommended, as shown in our cases.
Keywords: corneal cyst; corneal surgery; epithelial implantation